A Conceptual Study on Prevention & Management of Covid -19 Pandemic with Special Reference to Janapadodwamsa - Anamika Khatana; Rakesh Khatana (Indian Journal of Forensic Medicine & Toxicology, 2021)
Introduction: Ayurveda being one of the oldest surviving Medical Tradition, has a key role to play inthis crucial situation.Covid-19 it is not a simple infectious disease it is a pandemic disease caused byCoronavirus which reflects in human but stay as a host in animals. These viruses contain seven differentstrains; of which SARS-COV-2 is responsible for Covid-19. Its spread through droplets via air dueto sneezing, cough, talking and direct or indirect contact with an infected patient such as handshake,touch surfaces contact by an infected person. This virus causes the severe acute respiratory syndrome.Its incubation period varies between 2 to 14 days, the disease can transmit from symptoms less personto person. Material & Methods: Covid-19research information was collected from the world healthorganization, books, research papers, journals. Ayurveda literature from reference books, internet, andopinions of experts utilize as a review. Observations and Results: COVID-19 can be provisionallyunderstood from the Ayurvedic perspective as v?takapha dominant sannip?tajvara of ?gantu originwith pitt?nubandha. The asymptomatic, presymptomatic, mild, moderate, severe and critical stages ofCOVID-19 with varying clinical presentations have been analysed on the basis of nid?na, do?a, d??ya,nid?napañcaka and ?a?kriy?k?la. Conclusion: It will be good to take preventive measures which boostour immunity in these times. Ayurveda extensive knowledge base on preventive care by which eachindividual can achieve by uplifting and maintain his or her immunity. In Ayurveda, Immunity comes underthe heading of Vyadhiksamatwa. In Ayurveda, many single drugs or compound formulation were mentionedas Rasayana to boost up Immunity (Bala or Vyadhiksamatwa).